Antibacterial Silver Nanoparticles produced by Nd:YAG Laser - Abd-Alwahab, Zainab I.; Rasheed, Bassam G. (Nahrain University College of Engineering Journal, 2015)
Q-switched Nd-YAG laser of wavelengths (1060, 532 and 322 nm) with energy in the range 200 to 1000 mJ and 1 Hz repetition rate was employed to synthesis silver nanoparticles using pulse laser ablation in liquid. Effect of laser wavelength has been studied for the fundamental, second and third harmonic generation. The experimental UV-Vis absorbance data were fitted with theoretical Mie-Gans model. It is found that the smaller silver nanoparticle of 12 nm capable to terminate both Staphylococcus and Streptococcus bacteria.